Impact of tourism development on the situation inside North Korea - Suszwalak, Oliwia (Boundaries and Spheres of Influence in Domestic Politics and International Relations, 2023)
This chapter describes the development of tourism in North Korea, highlighting the specific nature of this country due to the adoption of doctrines such as Juche and Songun, which effectively isolated it from the rest of the international society. The purpose of the chapter is to prove that the development of tourism and the increasing number of tourists coming to the DPRK each year will not lead to political changes, because it is the specific conditions prevailing in this country that attract most visitors. To this end, tourists' motivations and impressions of their stay in the DPRK are examined, as well as the importance of the tourism sector to the government, what benefits it brings to it and how it is developed, while remaining under strict control at all times. The experiences of tourists from Western countries and China, who constitute the vast majority of visitors to North Korea, are analyzed and compared.